2021
DOI: 10.1371/journal.pone.0254571
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial heparin-binding hemagglutinin (HBHA)-induced interferon-γ release assay (IGRA) for discrimination of latent and active tuberculosis: A systematic review and meta-analysis

Abstract: Background The Mycobacterial heparin-binding hemagglutinin (HBHA) is an important latency-associated antigen that can be used to distinguish between latent tuberculosis infection (LTBI) and active tuberculosis (ATB). Although many studies were explored the efficiency of the HBHA-induced interferon-γ release assay (IGRA) in different populations, the clinical differential value of HBHA-IGRA is still controversial. Therefore, the aim of this study was to determine whether the HBHA-IGRA can be used as an efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Preventive therapy to HIV-infected participants reduced the prevalence of PCR-detected Mtb from 95% at baseline to 54% post-treatment (Belay et al, 2021). Experimental in vitro tests based on the detection of IFN-γ to heparin-binding hemagglutinin antigen (HBHA) have been shown interesting results as associated with Mtb containments and as tools to monitor active TB clinical states in children (Sali et al, 2018) confirming results from the adults (Delogu et al, 2011;Chedid et al, 2021;Chiacchio et al, 2017;Tang et al, 2021). Further studies to evaluate the ability of these approaches to predict TB development are needed (Table 1).…”
Section: Experimental Tests For Identifying Progressor To Tb Diseasementioning
confidence: 82%
“…Preventive therapy to HIV-infected participants reduced the prevalence of PCR-detected Mtb from 95% at baseline to 54% post-treatment (Belay et al, 2021). Experimental in vitro tests based on the detection of IFN-γ to heparin-binding hemagglutinin antigen (HBHA) have been shown interesting results as associated with Mtb containments and as tools to monitor active TB clinical states in children (Sali et al, 2018) confirming results from the adults (Delogu et al, 2011;Chedid et al, 2021;Chiacchio et al, 2017;Tang et al, 2021). Further studies to evaluate the ability of these approaches to predict TB development are needed (Table 1).…”
Section: Experimental Tests For Identifying Progressor To Tb Diseasementioning
confidence: 82%
“…The lack of a commercialized WB-HBHA-IGRA used here limits standardization of the assay for larger studies. Interest in the HBHA-IGRA was reported independently by several groups, mostly as an option to differentiate LTBI from aTB ( 10 13 , 15 , 30 32 ). However, technical differences between those studies, including different sources of HBHA, make comparisons of the results difficult.…”
Section: Discussionmentioning
confidence: 99%
“…However, technical differences between those studies, including different sources of HBHA, make comparisons of the results difficult. This might be mitigated by using a standardized, commercial WB-HBHA-IGRA, as recently stressed ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Even though IGRA evaluation studies and its recommendations required many years, effort, funding, and resources across the globe, it did not have a major contribution to successful tuberculosis control [13]. A recent meta-analysis has shown that heparin-binding hemagglutinin (HBHA) is a latency-associated Mtb antigen and HBHA-induced IGRA can be a promising diagnostic test to differentiate latent and active TB [29]. IGRA testing is also a cost-effective screening method [30].…”
Section: Interferon Gamma Release Assaysmentioning
confidence: 99%